Augustus Polonus. The Image of the Emperor in Polish Historiography in Inter-War Period. Preliminary Remarks - Gillmeister, Andrzej (Studia Ceranea, 2016)
The figure of the first Roman emperor in many ways had an impact on the Polish culture, especially in historiography and literature. In my paper I focus on some issues connected with the subject. I discuss the ideas presented by Tadeusz Zieliński, one of the most eminent researchers of the ancient world in Europe in the first part of 20th century. He devoted a significant part of his opus to present his own vision of Augustus seen as a reformer of the Roman state religion. Zieliński built the emperor’s image as the saviour of the Roman world in the face of „the end of times”. This term played significant role in Zieliński’s thinking about Roman history at the end of the Republic. For the Polish scholar celebration of the secular game in 17 BC was the final task done by Augustus. This task Zieliński defined as the sacred mission and connected with the figure of Sibyl and the impact of the Etruscan theory of saeculum. For Zieliński, Augustus belonged to the most important men of providence in Roman history. In the same way I discuss the ideas presented by Ludwik Piotrowicz and Mieczysław St. Popławski. Both scholars analised the question of imperial cult in depth. Popławski expressed original view on Augustus apotheosis seen as the development of imperial cult in transcendental perspective. Piotrowicz instead saw this problem as a purely political phenomenon. Last part of my paper is devoted to short resentation of the echos of Augustus’ bimillenium in Polish scholar activity.